Evaluation of the impact of delayed centrifugation on the diagnostic performance of serum creatinine as a baseline measure of renal function before antiretroviral treatment - Chikomba, Chemedzai Esnath (My University, 2020)
Background: The measurement of serum creatinine is a standard requirement of the medical management of people living with HIV. Renal dysfunction is common, both as a complication of HIV-infection and as a result of its treatment. The detection of abnormal renal function before the start of antiretroviral therapy will impact patient management and the outcome of treatment. Objectives: This study aimed to determine if a time delay in the centrifugation of serum samples affected the creatinine level and the estimated glomerular filtration rate as recorded on the analytical platforms used in the laboratory. Methods: Twenty-two (n = 22) HIV-positive, newly diagnosed and treatment-naïve patients were randomly recruited from Alexandra Health Clinic, Johannesburg, South Africa. Serum samples were centrifuged at six time intervals following receipt of the sample viz. < 4 h (baseline), 6 h, 24 h, 48 h, 72 h and 96 h. Creatinine concentrations were measured on the Roche platform utilizing the enzymatic and kinetic Jaffe methods. Whole blood samples were also analysed with the Abbott i-STAT point-of-care instrument. The estimated glomerular filtration rate was calculated using the Cockcroft Gault, CKD–Epidemiology Collaboration and Modified Diet and Renal Disease v3/4 equations. Results: At baseline (< 4 h) there was good agreement between the enzymatic and kinetic Jaffe methods: bias 1.7 μmol/l. The enzymatic and i-STAT creatinine concentrations were stable over 96 h viz. changes of 1.8% and 5.7%. However, from 24 h onwards agreement between the enzymatic and kinetic Jaffe methods was poor with the latter measuring 43.7 μmol/l higher than the enzymatic method at 96 h. Creatinine concentrations measured with the kinetic Jaffe method increased significantly in samples centrifuged after 6 h (p < 0.001, 61.7% change), and resulted in a 95% decline in eGFR at 96 h as determined with the CKD–Epidemiology Collaboration equation. Conclusion: The analysis of serum creatinine using the isotope dilution mass spectrometry traceable kinetic Jaffe method is unreliable if performed on samples centrifuged ≥ 6 h after collection. The raised creatinine concentration can affect clinical decisions such as renal functional assessment, choice of antiretroviral drug or regimen, and the dose and frequency of medication.
dissertation submitted in partial fulfilment of the requirements for the Degree of Master of Medicine (MMed) to the Faculty of Health Sciences, University of Witwatersrand, Johannesburg, 2020